2021
DOI: 10.3390/inorganics9070054
|View full text |Cite
|
Sign up to set email alerts
|

Isomeric 4,2′:6′,4″- and 3,2′:6′,3″-Terpyridines with Isomeric 4′-Trifluoromethylphenyl Substituents: Effects on the Assembly of Coordination Polymers with [Cu(hfacac)2] (Hhfacac = Hexafluoropentane-2,4-dione)

Abstract: The isomers 4′-(4-(trifluoromethyl)phenyl)-4,2′:6′,4″-terpyridine (1), 4′-(3-(trifluoromethyl)phenyl)-4,2′:6′,4″-terpyridine (2), 4′-(4-(trifluoromethyl)phenyl)-3,2′:6′,3″-terpyridine (3), and 4′-(3-(trifluoromethyl)phenyl)-3,2′:6′,3″-terpyridine (4) have been prepared and characterized. The single crystal structures of 1 and 2 were determined. The 1D-polymers [Cu2(hfacac)4(1)2]n·2nC6H4Cl2 (Hhfacac = 1,1,1,5,5,5-hexafluoropentane-2,4-dione), [Cu(hfacac)2(2)]n·2nC6H5Me, [Cu2(hfacac)4(3)2]n·nC6H4Cl2, [Cu2(hfacac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…have commented: “Planar bis(β‐diketonato) complexes can accept additional ligands at the axial sites keeping their planar structures.” [78] This preference (while not guaranteed) can be used to direct the assembly of 1D‐coordination polymers and circumvents the competitive assembly of metallamacrocycles when using 4,2′:6′,4“‐tpy ligands (see Section 2.4). This strategy is demonstrated in [Co(acac) 2 ( 20 )] n ( Figure 17 a ), [78] [Cu(hfacac) 2 ( 46 )] n ( Figure 17 b ), [79] [Cu(hfacac) 2 ( 47 )] n , [79] [Cu(hfacac) 2 ( 48 )] n , [80] and [Cu(hfacac) 2 ( 49 )] n , [80] (all structurally like [Cu(hfacac) 2 ( 46 )] n , Figure 17 b ). While the structure of [Zn(acac) 2 ( 50 )] n ( Figure 17 c ) resembles those cited above, it is noteworthy that 4′‐(4‐(pyrimidin‐5‐yl)phenyl)‐4,2′:6′,4′′‐terpyridine ( 50 ) coordinates through one pyridine and one pyrimidine ring rather than through the outer rings of the 4,2′:6′,4′′‐tpy domain [81] …”
Section: Directing 1d‐assembliesmentioning
confidence: 96%
See 2 more Smart Citations
“…have commented: “Planar bis(β‐diketonato) complexes can accept additional ligands at the axial sites keeping their planar structures.” [78] This preference (while not guaranteed) can be used to direct the assembly of 1D‐coordination polymers and circumvents the competitive assembly of metallamacrocycles when using 4,2′:6′,4“‐tpy ligands (see Section 2.4). This strategy is demonstrated in [Co(acac) 2 ( 20 )] n ( Figure 17 a ), [78] [Cu(hfacac) 2 ( 46 )] n ( Figure 17 b ), [79] [Cu(hfacac) 2 ( 47 )] n , [79] [Cu(hfacac) 2 ( 48 )] n , [80] and [Cu(hfacac) 2 ( 49 )] n , [80] (all structurally like [Cu(hfacac) 2 ( 46 )] n , Figure 17 b ). While the structure of [Zn(acac) 2 ( 50 )] n ( Figure 17 c ) resembles those cited above, it is noteworthy that 4′‐(4‐(pyrimidin‐5‐yl)phenyl)‐4,2′:6′,4′′‐terpyridine ( 50 ) coordinates through one pyridine and one pyrimidine ring rather than through the outer rings of the 4,2′:6′,4′′‐tpy domain [81] …”
Section: Directing 1d‐assembliesmentioning
confidence: 96%
“…Ligand 52 (Scheme 16) adopts conformation II (Scheme 4) in [Cu(hfacac) 2 (52)] n and the structure of the 1D-coordination polymer resembles that of [Cu 2 (OAc) 4 (34)] n (34 with R = n-hexyl or n-heptyl), [Cu 2 (OAc) 4 (38)] n , [Cu 2 (OAc) 4 (39)] n , and [Cu 2 (OAc) 4 (40)] n (compare Figures 18a and 12c, and see Table 1). [80] In contrast, ligand 53 exhibits conformation I (Scheme 4) in [Cu(hfacac) 2 (53)] n and the 1D-chain resembles that of [Cu 2 (OAc) 4 (34)] n (34 with R = Me) shown in Figure 12b. [80] Conformer I is also observed for the 3,2':6',3''-tpy unit in [Cu-(hfacac) 2 (54)] n , but in this case, a cis-arrangement of Ndonors at the Cu(II) center is observed (Figure 18b).…”
Section: A Preference For Trans-or Cis-{m(acac) 2 (N) 2 } and {M(hfac...mentioning
confidence: 99%
See 1 more Smart Citation
“…This journal is © The Royal Society of Chemistry 2022 (hfacac) 4 (L2) 2 ] n •nC 6 H 5 Cl the 3,2′:6′,3″-tpy domains exhibit conformation C, while with [Cu(hfacac) 2 (L2)] n •nC 6 H 5 Cl conformation B is adopted (Scheme 1). 26 Structures of ligands L1 and L2 are shown in Scheme 2.…”
Section: D-coordination Polymersmentioning
confidence: 99%
“…The theme of copper coordination polymers is continued in the paper by Housecroft et al, which elegantly demonstrated how ligand conformation can dictate the way in which coordination polymers pack, even when such packing is governed by relatively weak intermolecular interactions [2]. The ligands in question are isomers of terpyridine (4,2 :6 ,4 and 3,2 :6 ,3 ), and it is the positions of the N donor atoms that are crucial in determining the type of 1D chain that is observed in the resulting coordination polymers formed by reactions with Cu(hfacac) 2 ]•H 2 O.…”
mentioning
confidence: 99%